Hmc Labeling Of Certain Types Of Graph - et. al., J. Gowri, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper we introduce a new graph labeling called HMC labeling. We investigate HMC labeling of Path, Star, Bistar graphs.